Imaging the noncentrosymmetric structural organization of tendon with Interferometric Second Harmonic Generation microscopy. - Rivard, M; Popov, K; Couture, C; Laliberté, M; Bertrand-Grenier, A; Martin, F; Pépin, H; Pfeffer, C; Brown, C; Ramunno, L; Légaré, F (2014)
We report the imaging of tendon with Interferometric Second Harmonic Generation microscopy. We observe that the noncentrosymmetric structural organization can be maintained along the fibrillar axis over more than 150 μm, while in the transverse direction it is ∼1-15 μm. Those results are explained by modeling tendon as a heterogeneous distribution of noncentrosymmetric nano-cylinders (collagen fibrils) oriented along the fibrillar axis. The preservation of the noncentrosymmetric structural organization over multiple tens of microns reveals that tendon is made of domains in which the ratio between fibrils with positive and negative polarity is unbalanced.